A Study On Ambulance Services And Emergency Care At Local Hospitals: Perception Of Clients And Health Care Providers. - Che Hamzah, Mohd Shaharudin Shah (2007)
This prospective study attempts to identify and evaluate the clients and other service care providers' perception towards emergency care and ambulance services for the year starting from January to December of 2004 at Hospital University Science Malaysia (HUSM) and Hospital Kota Bharu (HKB), now known as the Hospital Raja Perempuan Zainab II (HRPZ II).Kajian prospektif ini bertujuan untuk mengenalpasti dan menilai tanggapan pelanggan dan kakitangan kesihatan yang lain terhadap perkhidmatan kecemasan dan ambulans.